A Bibliometric Study of Software Architecture - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
This study provides a comprehensive bibliometric analysis of software architecture research to map its intellectual structure, collaboration patterns, and thematic evolution. Data were collected from the Scopus database, covering publications from 2000 to 2026. The analysis employs quantitative bibliometric techniques and network visualization using VOSviewer, including co-authorship, citation, keyword co-occurrence, overlay, and density analyses. The results indicate that software architecture research has experienced substantial growth, characterized by increasing global collaboration and the emergence of dominant research hubs such as China, the United States, and India. Citation analysis highlights that the most influential studies are largely driven by technological tools, frameworks, and artificial intelligence innovations, reflecting a shift toward application-oriented research. Furthermore, keyword analysis reveals that while traditional topics such as architectural design and system performance remain central, emerging themes such as machine learning, cloud computing, and interdisciplinary applications—particularly in bioinformatics—are gaining prominence. The overlay and density visualizations confirm a temporal transition toward more adaptive, efficient, and data-driven architectural paradigms. Overall, this study contributes to a deeper understanding of the development and current trends in software architecture research, offering insights into future directions and supporting strategic research planning in this rapidly evolving field.